Culturally adaptive storytelling method to improve hypertension control in Vietnam - "We talk about our hypertension": study protocol for a feasibility cluster-randomized controlled trial. Issue 1 (December 2016) - Allison, Jeroan; Nguyen, Hoa; Ha, Duc; Chiriboga, Germán; Ly, Ha; Tran, Hanh; Phan, Ngoc; Vu, Nguyen; Kim, Minjin; Goldberg, Robert
Abstract Background Vietnam is experiencing an epidemiologic transition with an increased prevalence of non-communicable diseases. At present, the major risk factors for cardiovascular disease (CVD) are either on the rise or at alarming levels in Vietnam; inasmuch, the burden of CVD will continue to increase in this country unless effective prevention and control measures are put in place. A national survey in 2008 found that the prevalence of hypertension (HTN) was approximately 25 % among Vietnamese adults and it increased with advancing age. Therefore, novel, large-scale, and sustainable interventions for public health education to promote engagement in the process of detecting and treating HTN in Vietnam are urgently needed. Methods A feasibility randomized trial will be conducted in Hung Yen province, Vietnam to evaluate the feasibility and acceptability of a novel community-based intervention using the "storytelling" method to enhance the control of HTN in adults residing in four rural communities. The intervention will center on stories about living with HTN, with patients speaking in their own words. The stories will be obtained from particularly eloquent patients, or "video stars, " identified during Story Development Groups. The study will involve two phases: (i) developing a HTN intervention using the storytelling method, which is designed to empower patients to facilitate changes in their lifestyle practices, and (ii) conducting a feasibility cluster-randomized trial to investigate the feasibility, acceptability, and potential efficacy of the intervention compared with usual care in HTN control among rural residents. The trial will be conducted at four communes, and within each commune, 25 individuals 50 years or older with HTN will be enrolled in the trial resulting in a total sample size of 100 patients. Discussion This feasibility trial will provide the necessary groundwork for a subsequent large-scale, fully powered, cluster-randomized controlled trial to test the efficacy of our novel community-based intervention. Results from the full-scale trial will provide health policy makers with practical evidence on how to combat a key risk factor for CVD using a feasible, sustainable, and cost-effective intervention that could be used as a national program for controlling HTN in Vietnam and other developing countries. Trial registration ClinicalTrials.gov. Registration number:https://clinicaltrials.gov/ct2/show/NCT02483780 (registration date June 22, 2015).